Long-Duration Carbon Dioxide Anesthesia of Fish Using Ultra Fine (Nano-Scale) Bubbles - Kugino, Kenji (PLoS One, 2016)
Introduction: We investigated whether adding ultrafine (nano-scale) oxygen-carrying bubbles to water concurrently with dissolved carbon-dioxide (CO(2)) could result in safe, long-duration anesthesia for fish. Results: To confirm the lethal effects of CO(2) alone, fishes were anesthetized with dissolved CO(2) in 20°C seawater. Within 30 minutes, all fishes, regardless of species, died suddenly due to CO(2)-induced narcosis, even when the water was saturated with oxygen. Death was attributed to respiration failure caused by hypoxemia. When ultrafine oxygen-carrying bubbles were supplied along with dissolved CO(2), five chicken grunts were able to remain anesthetized for 22 hours and awoke normally within 2–3 hours after cessation of anesthesia. Conclusions: The high internal pressures and oxygen levels of the ultrafine bubbles enabled efficient oxygen diffusion across the branchia and permitted the organismal oxygen demands of individual anesthetized fish to be met. Thus, we demonstrated a method for safe, long-duration carbon dioxide anesthesia in living fish under normal water temperatures.